Parathormone Levels in a Middle-Eastern Healthy Population Using 2nd and 3rd Generation PTH Assays - Marie-Hélène Gannagé-Yared; Marie-Noëlle Kallas-Chémaly; Ghassan Sleilaty (International Journal of Endocrinology)
Background. The purpose of the current study is to determine PTH reference values in vitamin-D-replete Lebanese adults using 2nd and 3rd generation PTH assays and to look at the factors that affect PTH variations. Methods. Fasting PTH was measured using 2nd and 3rd generation Diasorin PTH assays in 339 vitamin-D-replete healthy subjects aged 18 to 63 years (230 men and 109 women) who have normal calcium levels and an eGFR ≥60 ml/mn. 25-OH vitamin D (25(OH)D) was measured using the Diasorin assay. Results. For the 2nd PTH generation, median (IQR) levels were 48.9 (34.9–66.0) pg/ml, and its 2.5th–97.5th percentile values were 19.7–110.5 pg/ml for 25(OH)D values between 20 and 30 ng/ml, and 19.7–110.7 pg/ml for 25(OH)D values ≥30 ng/ml. For the 3rd PTH generation, the median (IQR) values were 23.9 (17.7–30.5) pg/ml, and its 2.5th–97.5th percentile values were, respectively, 9.2 and 50.2 pg/ml for 25(OH)D values between 20 and 30 ng/ml, and 8.4 and 45.4 pg/ml for 25(OH)D values ≥30 ng/ml. The median (IQR) serum 25(OH)D levels were 27.5 (23.8–32.7) ng/ml. 2nd and 3rd generation PTH values are strongly correlated (r = 0.96, p<0.0001), but poorly concordant (Lin’s concordance coefficient 0.365, 95% CI: 0.328–0.401) with observations beyond the 95% Bland–Altman limits of agreement. 2nd and 3rd generation PTH levels did not differ according to gender and were significantly correlated with age but not with 25(OH)D and serum calcium levels. Conclusion. Lebanese adult healthy subjects have higher 2nd and 3rd generation PTH levels compared with the reference range provided by the manufacturer. The reference range was not influenced by changing the 25(OH)D cutoff. The clinical significance of the higher PTH levels in our population should be investigated.